Annualized bleeding rate in hemophilia A patients in Brazil: a systematic review - Alessandra NL Prezotti; Débora MC Rocha; Endi L. Galvão; Thaís Gimenez; Leo Sekine; Rodrigo A. Ribeiro; Elisa Sobreira (Hematology, Transfusion and Cell Therapy)
Background: Hemophilia A is an X-linked chronic bleeding disorder due to deficiency of the coagulation factor VIII. According to the residual level of FVIII activity, patients can present with severe (FVIII levels <1 %), moderate (1–5 %) or mild (6–40 %) phenotypes. While long-term prophylaxis is the current standard of care and has been shown to be effective in minimizing bleeding episodes, episodes of hemarthrosis, that could lead to arthropathy and disability, are still reported. This systematic review aimed to evaluate available data concerning current treatment outcomes in severe hemophilia A patients without inhibitors in Brazil, focusing on the frequency of bleeding episodes and adherence to therapy of patients under prophylactic treatment. Method: A literature search strategy was used in the MEDLINE (via PubMed), Embase, LILACS and SciElo databases from 2014 onwards, since it was the moment that prophylaxis effectively became available in the Brazilian National Health Service, even though prophylactic treatment had been officially incorporated in 2011 focused on concerning bleeding episodes and adherence rate of this population. Results: Searches yielded 536 articles. After removal of duplicates, 417 articles were screened for eligibility. Eventually, 104 articles were selected for full-text assessment. Finally, only five publications met eligibility criteria and were selected for the descriptive review. Conclusion: Available information on efficacy of severe hemophilia A management in Brazil currently relies on scarce and possibly biased information. It should be strongly emphasized that Brazil is in great need of a structured and coordinated effort to improve collection, analysis, and reporting of data on hemophilia A patients.